جودة الخدمات التعليمية وأثرها على رضا الطلبة - عبد السلام البهيليلوسيم محمد (Aljameai, 2026)
المستخلص: استهدف البحث بصفة أساسية التعرف على أثر جودة الخدمات التعليمية المقدمة في كلية الزراعة بجامعة طرابلس على مستوى رضا الطلبة، مع تقييم واقع تلك الخدمات وتحديد العوامل المؤثرة في تقدير الطلبة لها، بما يُسهم في تحسين المخرجات التعليمية، وقد إستند البحث على بيانات أولية جُمعت من طلبة الكلية عبر استبانة أُعدّت لتوفير المعلومات اللازمة لتحليل موضوع الدراسة، إلى جانب بيانات ثانوية ذات صلة، وقد استُخدِمَ التحليل الاقتصادي القياسي بتطبيق نموذج الانحدار اللوجستي الثنائي (Binomial Logistic Regression) بهدف التنبؤ بإمكانية تحسين مستوى الخدمات التعليمية في منطقة الدراسة، اعتمادًا على مجموعة من المتغيرات المستقلة مقابل متغير تابع يتمثل في مستوى جودة الخدمات التعليمية المقدمة للطلبة، وأظهرت النتائج أن تحسين مستوى الخدمات المرتبطة بإدارة المكتبة، وقاعات ومرافق الكلية، ومعالجة مشكلات تسجيل المقررات الدراسية، ومدى توفر الحاسوب لإستخدامات الطلبة يُسهم في رفع جودة الخدمات التعليمية المقدمة، حيث بلغت نسب التحسن 88%، 83%، 34% على الترتيب. Abstract: The study aimed to identify the impact of the quality of educational services which provided by the Faculty of Agriculture at University of Tripoli for student satisfaction, through their evaluation of the quality of the services which provided to them. In addition, to identifying the importance of factors that students use in evaluating the quality of those services in order to achieve their satisfaction. Thus, developing the quality of the educational product. The study relied on the primary data which collected from the College of Agriculture at University of Tripoli, based on an interview and a questionnaire form to provide the amount of necessary data to analyze the study, which is not available in secondary data. It relied on the econometric analysis method by using Binomial logistic regression model to achieve the goals, and to predict the possibility of developing the educational services level in the study area, where several independent variables were used against one dependent variable, which is the quality of educational services for students. The results of the study indicate the following: Increasing or improving the levels of (the administration of library, halls and facilities in the college, solving the problems of course registration in appropriate way, the health facilities and student breaks) raises the probability of increasing the quality of services which provided to students 88%، 83%، 34% percentage in the same order.